(untitled) (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2025)
The article examines the peculiarities of the emergence and development of design as a phenomenon of artistic culture of the modern stage of the urbanization process and its gradual spread to the urban environment in the conditions of the post-industrial city during the period of the change of technological eras. At the same time, the urban environment is understooding as an extremely multi-layered concept that is the object of research in many sciences - urban planning, ecology, economics, sociology. It is the "multi-layeredness" of the urban environment that allows us to see the features of its modern state, related to the legacy of the industrial period, and to propose the use of urban design for its improvement. In such conditions, the activity of urban design is aimed, first of all, at the formation of open public spaces - squares, streets, embankments, gardens, parks, etc., in which anthropogenic or natural elements prevail, covers transport and engineering infrastructure - practically the entire functional and planning organization of the city and its subject-spatial content. At the same time, a number of public spaces, such as streets, boulevards, embankments, are elements of the structural framework of the city, and such as squares, gardens, parks are systemforming nodes. That is, the newest components of urban design, including landscape design, become system-forming elements of open public spaces in a unified system of structural and planning organization of the city. Under the influence of urban design as a project-artistic activity, open public spaces in the structure of the city undergo a positive transformation based on complex modeling of their aesthetic, functional and social components. At the same time, their system-forming role increases. Taking into account that in modern conditions, preference is given to the reproduction of the environment of the city’s historical core and the adjacent territories of the public center, the objectively manifested structuring of the postindustrial city allows us to talk about the need to shift the emphasis to the restoration of public spaces in all structural elements of the city with the strengthening of their importance as urban planning nodes or frame elements. For this, it is proposed to determine the urban planning (structural and planning) expediency of carrying out the restoration of the territory, taking into account the historical and functionaltypological projection of the environment on the selected territory, creating its aesthetic and exclusive attractiveness and compliance with social demands.